Life Skills-Based Leadership Strategy in Improving Madrasah Quality: A Case Study - Tamsilu, Takdir; Rustan, Rustan; Kartini, Kartini (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This research is based on the urgency of strengthening life skills in madrasahs so that graduates excel academically and adapt to contemporary socio-techno-economic challenges. This study intends to analyze life skills-based leadership strategies to improve the quality of State Elementary Madrasah 01 Luwu and identify obstacles and their solutions. The design used is qualitative-descriptive with purposive selection of informants (madrasah principals, teachers, and students); data were collected through observation, interviews, and documentation studies, and their credibility was tested through triangulation and member checks. The findings show leadership strategies that combine transformational, participatory, and situational characters—including teacher empowerment through training/collaboration, integration of life skills into the curriculum and contextual activities (e.g., “Cheerful Friday Market” and morning talk), and strengthening a character-oriented school culture. These strategies contribute to increased student self-confidence, discipline, responsibility, and participation, which impacts the quality of learning. The main obstacles include limited human resources and facilities, diverse parental support, a dense curriculum, and substandard life skills evaluations. Life skills-based leadership is effective in improving madrasah quality when implemented systematically, integrating curriculum, teacher development, school culture, and partnerships. Practical implications include the need for standardized life skills evaluations, teacher capacity building, and resource support. Further research is recommended to test this model comparatively across madrasahs and develop validated life skills assessment instruments.